Effectiveness and safety of moisturizing wash and cream in the treatment of elderly xerosis cutis - Legiawati, Lili; Yusharyahya, Shannaz Nadia; Astriningrum, Rinadewi; Puteri, Fathirah Rahmatiah; Ilyas, Nabila Chalisya (UI Scholars Hub, 2025)
Background: The skin undergoes degenerative and metabolic changes with aging, increasing susceptibility to dermatological conditions. Xerosis cutis, characterized by rough, scaly skin on the lower legs, is the most common cause of pruritus in elderly patients, with a prevalence of 38–85%. Treating xerosis cutis is challenging due to its multifactorial causes, especially in the elderly. Moisturizers remain the primary and most effective treatment, providing convenience and efficacy. This study aimed to evaluate the effects of QV Intensive Moisturizing Cleanser™️ and QV Intensive Cream™️ (Ego Pharmaceuticals, Australia), which contain humectants, emollients, and occlusives. Case Illustration: This observational case series involved six elderly subjects (>60 years) with xerosis cutis. Exclusion criteria included medications that cause dry skin, use of topical moisturizers within 2 weeks, or oral supplements (hyaluronic acid, vitamin C, and ceramide) within 4 weeks before the study. Over four weeks, subjects used only the specified cleanser and moisturizer on affected skin. Improvement was assessed subjectively using the Smoothness, Redness, Roughness, Cracking (SRRC) score, the Dermatology Life Quality Index (DLQI), and the 5D Pruritus Scale. Objective measures included transepidermal water loss (TEWL) via Tewameter® TM300 and skin capacitance (SCap) via Corneometer® CM825 (Courage+Khazaka Electronic GmbH, Germany). Discussion: All subjects showed improvement in SRRC, 5D Pruritus Scale, DLQI, TEWL, and SCap after four weeks of cleanser and moisturizer use, with no side effects or irritation observed. Conclusion: Cleansers and moisturizers containing humectants, emollients, and occlusives were found to be safe and effective for treating xerosis cutis in geriatric patients.